Monthly assessment of the relative abundance and development of immature stages of culex mosquitoes (Diptera: Culicidae) of the selected breeding habitats in Niger, Nigeria - Abu Hassan Ahmad; Shehu, Ibrahim Kura; Hamdan Ahmad; Intan Haslina Ishak; Salim, Hasber; Kayode, Olayemi Israel; Solomon, Danjuma; Yakudima, Ismaila Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2022)
The information on relative abundance and distribution of Culex mosquitoes are essential for determining illness risk and this is especially critical when a disease spreads quickly and that prompt assessments for disease mitigation techniques are required. This study was conducted to assess and provide an epidemiological report on the relative abundance and development of immature stages of Culex in conventional larval breeding habitats in selected LGAs of Niger State, Nigeria. Gutter, swamps, and large water bodies were chosen as larval habitats, and samples were taken weekly from May to November 2019. The findings revealed the presence of three vector mosquito species in the areas namely: Culex quinquefasciatus (887.25±121.7), Cx. nigripalpus (434.50±46.34) and Cx. salinarius (351.92±32.48). Habitats-wised showed large water habitats had the abundance of Culex (686.75±98.11) followed by gutters (516.67±60.20) and the least was swamps (471.25±42.08) mosquitoes. Based on the monthly abundance rate (MAR), the peak abundance of the immature stages was June and July and declined in November in both habitats. While the age survival rate (ASR) differed significantly (P0.05) from one another for L1 and L4 except for the L3 immature stage that was differentiated with la ecosystem are causing a severe hazard of culex-borne diseases (CBD) to public health in Niger State.